Anatomy of Risk Premium in UK Natural Gas Futures - Beatriz Martínez; Hipòlit Torró (Fondazione Eni Enrico Mattei (FEEM), 2016)
In many futures markets, trading is concentrated in the front contract and positions are rolled-over until the strategy horizon is attained. In this paper, a pair-wise comparison between the conventional risk premium and the accrued risk premium in rolled-over positions in the front contract is carried out for UK natural gas futures. Several novel results are obtained. Firstly, and most importantly, the accrued risk premium in rollover strategies is significatively larger than conventional risk premiums and increases with the time to delivery. Specifically, for strategy horizons between three and six months, this difference increases from 1% to 10%. Secondly, it is the first time that risk premium in day-ahead futures has been measured in this market. The average value of the day-ahead risk premium is 0.5% per day and it is statistically significant. Thirdly, all risk premiums are significantly larger and more volatile in winter. Finally, risk premium time-variation is analyzed using a regression model. It is shown that reservoirs, weather, liquidity, volatility, skewness, and seasons are able in all cases to explain between 21% and 59% of the risk premium time-variation (depending on the futures maturity and sub-period).
Keywords: G13; L95; 330; Natural Gas Market; Futures Premium; Rollover; Seasonal Risk Premiums